THE EFFECT OF STRATEGIC ECONIMIC MANAGEMENT AND LEADERSHIP STYLES ON JOB SATISFACTION AND ITS IMPLICATIONS ON EMPLOYEE PERFORMANCE (Survey in Teklom Divre III, West Java) - Ony Djogo; Eplhis Rudy (JEES: Journal of Economic Empowerment Strategy, 2021)
This research aims to find out, analyse and review the strategic management, leadership style, job satisfaction and employee performance and influence of strategic management and leadership style towards job satisfaction and implications on employee performance. The method used in this research uses the Explanatory Survey method, the data analyzed using the path analysis technique. Based on the analysis of the research results, obtained the following findings, stratejic management is in the category good towards. Very good job satisfaction is in the category of good towards very good and employee performance is in the category good towards very good. Stratejic management and leadership style have both partial and simultaneous positive influences on job satisfaction, and job satisfaction has a positive and significant influence on employee performance,